2020
DOI: 10.1371/journal.pgen.1008484
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mutations that confer resistance to 2-deoxyglucose act through Hxk2 and Snf1 pathways to regulate gene expression and HXT endocytosis

Abstract: Yeast and fast-growing human tumor cells share metabolic similarities in that both cells use fermentation of glucose for energy and both are highly sensitive to the glucose analog 2deoxyglucose. Spontaneous mutations in S. cerevisiae that conferred resistance to 2-deoxyglucose were identified by whole genome sequencing. Missense alleles of the HXK2, REG1, GLC7 and SNF1 genes were shown to confer significant resistance to 2-deoxyglucose and all had the potential to alter the activity and or target selection of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(67 citation statements)
references
References 61 publications
(124 reference statements)
7
60
0
Order By: Relevance
“…As would be expected from our current knowledge of 2-DG toxicity, in which 2-DG-6-P plays a pivotal role, the isolation of spontaneous 2-DG-resistant budding yeast strains consistently retrieved hexokinase mutants (Table 1) [196,32,19,64,71,186] and indeed, deletion of the main hexokinase gene HXK2 results in 2-DG resistance [35,64]. This is also the case in many other species, such as in the thermotolerant yeast Kluyveromyces marxianus [197], Kluyveromyces lactis [187], Schizosaccharomyces pombe [68] and others.…”
Section: -Dg Phosphorylationmentioning
confidence: 58%
See 3 more Smart Citations
“…As would be expected from our current knowledge of 2-DG toxicity, in which 2-DG-6-P plays a pivotal role, the isolation of spontaneous 2-DG-resistant budding yeast strains consistently retrieved hexokinase mutants (Table 1) [196,32,19,64,71,186] and indeed, deletion of the main hexokinase gene HXK2 results in 2-DG resistance [35,64]. This is also the case in many other species, such as in the thermotolerant yeast Kluyveromyces marxianus [197], Kluyveromyces lactis [187], Schizosaccharomyces pombe [68] and others.…”
Section: -Dg Phosphorylationmentioning
confidence: 58%
“…Previous work showed that the affinity of yeast hexokinase preparations towards 2-DG is in the same range as that for glucose [41,199,200] and recent work further showed that both hexokinases had a similar activity toward 2-DG in vitro [186]. This goes against the idea that 2-DG is not phosphorylated in hxk2∆ cells.…”
Section: -Dg Phosphorylationmentioning
confidence: 95%
See 2 more Smart Citations
“…While Snf1 regulation of Mig1 (not show) alleviates repression of some genes in response to 2DG, other transcriptional responses to 2DG likely to occur via Snf1-independent signaling pathways Zimmermann and Scheel 1977). More recent studies in yeast have focused on defining mechanisms of 2DG-resistance in cells growing on glucose, which is more germane to what a cancerous cell would experience (Defenouillere et al 2019;McCartney et al 2014;O'Donnell et al 2015;Ralser et al 2008;Soncini et al 2020).…”
Section: Yeast As a Model To Understand The Cellular Impact Of 2dgmentioning
confidence: 99%